A Review on the Text Segmentation Techniques (International Journal of Engineering and Computer Science, 2017)
This paper represents the text segmentation is an important process of image processing and understanding. Basically it is defined as the process of dividing the image into different parts of homogeneity. The aim of text segmentation is to simplify the representation of an image into something that is more meaningful and easier to understand.So the overall objective is to represent the nearest neighbor criteriaon for grouping components in the same line which results in clusters as well as large dataset containing variety of images .The Sobel and Laplacian for enhancing degraded low contrast pixels in it.